2020
DOI: 10.18203/2349-3933.ijam20205470
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of severity of retinal hard exudates and its association with systemic risk factors

Abstract: Background: Diabetic macular edema (DME) characterized by deposition of hard exudates in central retina is now the leading cause of visual loss in persons with diabetes mellitus. Several studies have shown association between severity of retinal hard exudates and various components of serum lipid. The aim of this study is to estimate the proportion of severity of retinal hard exudates with risk factors like dyslipidemia, duration of diabetes, hypertension, HbA1c levels and microalbuminuria.  Methods: A hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[76] Silpa D et al (2021) reported that the mean HbA1c was 7.56%. 16 Renal Function Tests: In group A, the mean blood urea was 14.27±4.39 mg/dl while in group B, it was 15.05±4.21 mg/dl (non-significant; p-value 0.423). In group A, the mean serum creatinine was 0.84±0.14 mg/dl while in group B, it was 0.84±0.13 mg/dl (non-significant; p-value 0.793).…”
Section: Biochemical Parametersmentioning
confidence: 91%
See 4 more Smart Citations
“…[76] Silpa D et al (2021) reported that the mean HbA1c was 7.56%. 16 Renal Function Tests: In group A, the mean blood urea was 14.27±4.39 mg/dl while in group B, it was 15.05±4.21 mg/dl (non-significant; p-value 0.423). In group A, the mean serum creatinine was 0.84±0.14 mg/dl while in group B, it was 0.84±0.13 mg/dl (non-significant; p-value 0.793).…”
Section: Biochemical Parametersmentioning
confidence: 91%
“…Prakash G et al (2016) reported that diabetic retinopathy patients had longer diabetes duration (11±1.8 years) than patients without diabetic retinopathy (9±2.5 years); pvalue 0.04. Silpa D et al (2021) reported that percentage distribution of the diabetic patients according to duration of diabetes showed 42.6% in15 years group. Mean duration of diabetes mellitus in the sample population was 12.7±5.4 years.…”
Section: Duration Of Diabetes Mellitusmentioning
confidence: 99%
See 3 more Smart Citations